Aspectos da produção cultural de Salvador: um estudo sobre os reflexos da atividade musical na economia local - PEREIRA, Claudia Fardin Soares (2014)
This research aimed to analyze aspects of the cultural production found in the society of Salvador, with special focus on the music segment, where we intended to identify effects on the jobs generation. For such, this study started from the formation of the cultural pillars, the importance of this production and its incentives. The work was structured from the following questions: what is the cultural production importance for the economy of Salvador? What are the effects of this production, especially from of the music segments, on the promotion of social welfare for the population of Bahia? Starting from the cultural formation elements, this search sought to study the music cultural production effects on the employment and income generation in Salvador - the territorial landmark of the work. This way, a qualitative study of exploratory and descriptive nature was made, in an attempt to understand the cultural formation process base and to investigate the participation, organization and articulation degree of the music segment in the Salvador society. Bibliographic research and interviews with the involved agents allowed the proposition of subsidies for a more focused reflection about this cultural activity practices in the capital of Bahia. One of the aspects raised by this work was directly connected to the informality of the activities within this segment, which resulted in problems for the necessary data collecting which would allow a good analysis of the proposed subjects. Along the research, some desarticulation between the public and private sectors that are responsible for the planning and the promotion of culture in this Capital was noticed, producing great impact on the professional activities, as well as on the results production, that are a lot below the expected potential. Even so, the research was able to see that in Salvador, the cultural segment, especially the music segment, is responsible for significant jobs generation, employment and income for the population.